The prosthetic implant of MBA Optetrak in the treatment of knee osteoarthritis: 5 years of experience - Pedrazzini, A.; Pogliacomi, F.; Scaravella, E.; Pompili, M.; Ceccarelli, F. (Acta Biomedica Atenei Parmensis, 2014)
In this study the authors report their experience in treating knee osteoarthritis with MBA Optetrak prosthetic implant, designed to minimize the stress of high density polyethylene. In all patients, we implanted two different Optetrak prosthesis according to the validity or not of the posterior cruciate ligament. At follow-up visit, which was performed after an average follow-up of 3.6 years, we analyzed 53 patients radiographically and clinically using the Knee Society Score (KSS). Depending on our experience, we consider mandatory to have a precise selection of the patients as well as to perform an accurate capsular and ligamentous balance during operation. Furthermore, the use of prosthesis models which are similar to the normal knee allows to obtain good and durable results.